Level of Formation of The Information Culture of Islamic Students - ANVAROV, ALISHER (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2024)
This article explains what information culture is and its specific features in the era of modern information culture. Fast and high-quality circulation of information is needed in the educational system and is an important factor or aspect for the progress and development of a country. Therefore, it is important for students and the younger generation to implement the basic criteria of information culture in the proper use of the Internet in education. The research problem is to determine the social factors that lead to the lack of a critical approach to the selection of necessary information among students in Islamic educational institutions. This research is important because information culture is a vital need for future preachers or preachers. The research method uses a literature review approach. The focus of the research is to analyze the patterns of using information culture on the Internet and social media. The results of the study provide an explanation of the patterns of information use in society, especially in Islamic educational institutions. The results describe 13 key factors on the level of formation of students' information culture in Islamic education in the 21st century. Keywords: Information Culture, Islamic Education Institutions